ANALISIS PENERAPAN PRINSIP 5C+1A DALAM PROSES PEMBERIAN PEMBIAYAAN MIKRO PADA BANK SYARIAH - Chasanah, Uswatun; Firmansyah , Muhibuddin (ILJ: Islamic Learning Journal, 2023)
Sharia Bank, inchanneling funds through financing, it is necessary to apply the principle of prudence todebtor, among which can be applied is p5C principles which include:Character, Capacity, Capital, Collateral, dan Condition of Economic. In addition, it is also necessary to consider aspects of 1A (Sharia) in decision making. The purpose of this study is to find out about the application of the 5C + 1A principles in the process of providing microfinance to Islamic banks.This study uses a qualitative method with a descriptive approach. By using two data sources, namely primary data obtained by conducting interviews with Islamic banks, secondary data obtained from literature, books, journals, the internet and previous research. In data analysis, the authors here use an inductive way of thinking that starts with data and information about the application of the 5C+1A principles in the process of providing microfinance to Islamic banks. The results of this study indicate that the application of the 5C+1A principles (Character, Capacity, Capital, Collateral, Condition of Economic and Sharia Aspects) in the process of providing microfinance to Islamic banks is carried out to prevent the process of providing financing that is not on target in order to minimize bad financing. However, even though the 5C + 1A principles have been implemented, bad/problem financing is sometimes unavoidable, so Islamic banks also need to implement a strategy for solving them.